Computed tomography-guided percutaneous biopsy in diagnosis of suspected metastatic renal cell carcinoma: which location is the most suitable - Hoffmann, Petr; Balík, Michal; Hoffmannová, Martina; Kopecký, Jindřich; Ryška, Pavel; Draganovičová, Jana; Dvořák, Petr (Wideochirurgia i Inne Techniki Mało Inwazyjne, 2024)
INTRODUCTION: Systemic targeted therapy options are commonly used in patients with metastatic renal cell carcinoma (mRCC). Histological verification is crucial for treatment of mRCC. AIM: Our aim was to evaluate an optimal location for percutaneous computed tomography‐guided biopsy in a diagnosis of suspected mRCC. MATERIALS AND METHODS: A total of 138 percutaneous biopsies for tumors ranging from 21 to 133 mm in diameter (median, 72 mm) were carried out in 134 patients with suspected mRCC over a 5‐year period. The biopsy location was variable, with kidney biopsy performed in 77 cases (55.8%), and other localizations (retroperitoneum, peritoneal cavity, liver, pelvis, pleural space, lung, mediastinum, chest or abdominal wall, and pancreas) in 61 cases (44.2%). RESULTS: As many as 288 biopsies (97.1%), yielded truepositive results, and 4 procedures (2.9%) yielded histologically falsenegative results that required confirmation through extended rebiopsy. RCC was the most common individual diagnosis (85.5%), with non‐RCC histology verified in 14.5% of cases. In total, 32 complications (23.2%) were confirmed, 2 of which were pneumothoraces, 29 were minor bleeding that needed only conservative management, and 1 case required angiography and embolization for hemorrhage treatment. While no significant relationship between the biopsy success and lesion localization (renal vs other) was found (P = 0.13), the relationship between complication rate and biopsy localization (renal vs other) was significant (P = 0.01). CONCLUSIONS: Lesion localization (renal vs other) was not relevant to histological accuracy of the biop‐ sies performed in patients with suspected mRCC. However, the biopsies of lesions outside the kidney had a lower complication rate.